The Dilemma of Handling The Covid-19 Pandemic in Islamic Sharia Province: The Challenge of Building Trust in Government - Adri Patria (Sekolah Pascasarjana Universitas Brawijaya, 2021)
The specialty of Aceh, which is closely related to the strength of Islamic values and norms, emphasizes the vital role of Teungku (Ulama) Aceh in maintaining the practice of these values and norms. This local wisdom has also become a dilemma for local government officials in Aceh in the context of preventing the Covid-19 pandemic in Aceh, even though various policy products have been created. This dilemma can be seen from the difficulty in realizing the responsibility of local government officials who are members of the Covid-19 Pandemic Handling Task Force, given the people's trust, which is more dominant Teungku's in their village in understanding and believing in the Covid-19 pandemic phenomenon itself—which of course has a dominant emphasis on conformity with Islamic values (one of which is seen in the difficulty of implementing congregational 'shaf shalat (prayer)' protocols in the pandemic era). Using Max Weber and John Locke's framework of thinking about legitimacy, this study seeks to answer why the implementation of the Covid-19 pandemic prevention health protocol is not working well in Aceh? The results of this study, which are guided by qualitative methods, indicate that the low legitimacy of local government officials is none other than due to the Acehnese public's low trust in the government in dealing with the Covid-19 pandemic itself, as well as showing the central role of Teungku in framing the understanding of the pandemic. The dominance of Teungku's understanding, which is contradictory to the understanding built by the government, has increasingly created momentum for people who did not comply with health protocols in the pandemic era, so it is not surprising then when mosques and stalls (cafes/restaurants) in the scope of the Aceh region are hardly implementing these health protocols, and where they exist, tends to be only part of maintaining the necessary formality. The government apparatus that is adhered to with the responsibility to protect society - with all the legal-formal policies that support it, is seen in a position of less power in framing the public's trust, so it requires a separate strategy to continue to prove its commitment to carrying out its duties and functions properly, but without straddle the values and norms of local wisdom inherent in Aceh.